“Beba menos, beba melhor”: um estudo da subcultura de consumo de cerveja artesanal e o sentimento de devoção do consumidor - Koch, Eduardo Salgueiro (2016)
The aim of this work is to identify, describe and analyze how the sentiment of consumer devotion is manifested in the subculture of craft beer consumption, exploring aspects related to consumption as a vehicle for transmission of symbolic meanings. The theoretical foundation which has supported this research addresses issues discussed in the literature with regard to culture and consumption (ARNOULD; THOMPSON, 2005; MCCRACKEN, 2003), the study of sentiments in the marketplace (GOPALDAS, 2014), the sentiment of consumer devotion PIMENTEL; REYNOLDS, 2004) and consumption subcultures SCHOUTEN; MCALEXANDER, 1995; KOZINETS, 2001; CELSI ET AL, 1993). This study has an explanatory and exploratory character, and it looks through the ethnographic method to explore the cultural universe that works as a background of the issues and then identify how the sentiment of consumer devotion manifests itself in a subculture of consumption. Data were collected over 1 year of field research conducted in craft beer events, fairs, bars and specialty restaurants, accompanying homemade beers productions and theme pubs in Rio de Janeiro and Porto Alegre. During the research, it was possible to collect information about the day-to-day members of this subculture and the relationships that are formed from this activity. Individual interviews were also conducted using a semi-structured script, aimed to understanding how these consumers find themselves within the subculture and how they interpret the craft beer as a lifestyle and values provider. It were conducted 38 interviews with consumers, both female and male, between ages 19 and 45 years, residents in the city of Rio de Janeiro and Porto Alegre, between January and November 2015. The findings presents that the sentiment of consumer devotion is present in a subset of the subculture entitled Pan´s because they are the members who more demonstrate similar values with the object and develop an affective commitment in addition to performing behaviors that sustain the condition of sacred object. Moreover, it was possible to identify other sentiments and discrete feelings acting in this subculture, which seems to be an indication that feelings can be considered as an emotional component of the subculture.